Morpho-syntactic Issues in As-Suhaili’s Book Neta’at Al-Fikr Fi Al-Nahw (Intellectual Output in Syntax) - Al-Bakri, Manal Fayez Abdullah (Arts for Linguistic & Literary Studies, 2023)
This study examines the morpho-syntactic issues in Abu Al-Qasim Abdulrahman Al-Suhayli’s book "Neta'at Al-Fikr", with particular focus on analyzing and discussing some selected morpho-syntactic topics from the book, highlighting Al-Suhayli's efforts and contributions to the field of morphology and syntax. The study is divided into an introduction, two sections and a conclusion. The introduction included a translation of Imam Al-Suhayli's biography and an overview of the field of morphology and syntax. Section one was concerned with Noun and infinitive Structures. Section two dealt with Verb structures. The study revealed that Al-Suhayli's dealt with morphological and syntactic issues at the morpho-syntax interface, as was customary among earlier syntacticians. It was concluded that he adhered to the Basri school of thought in some of his opinions and preferences regarding morpho-syntactic matters, and showed a particular interest in stylistics when explaining certain forms, their meanings, letters, and diacritical marks.